Desing and simulation of integrated circuit of the neuronal network aplication to control of motors velocity DC - Utrilla Salazar, Darío (2018)
The objective of this work, is the development of an integrated device, that allows to control the speed of a motor of DC (DC), using a neuronal network. In the present report a developed design is described to control this type of motors DC using the method of training with algorithms of retropropagacion through the plant. Also considering that can be trained to a neuronal network to control a dynamic process with variable parameters. Shaping in a physical device of an integrated circuit developed with tools of advanced digital design.